The political writings of Bhagat Singh - Bhagat Singh 1907-1931 (Monthly Review Press, 2024)
"The young martyr Bhagat Singh is a legend of the Indian anti-colonial struggle. He was not just a man of action, but of great intellect and deep insight. While still in his early teens, he showed a depth of understanding of Indian political reality. He read widely and became fluent in several Indian languages, as well as English. Moreover, he wrote insightful political essays, ones that a much older person would have been proud to have written. It is not only that his call to arms against the British imperialists inspired Indians - young and old. It is that his written works continue to stir the minds of all those who seek a world where everyone is equal, and all can fully develop their capacities. He is as much a part of the Indian radical tradition today as he was one hundred years ago."
"Originally published in India by LeftWord Books" © LeftWord Books 2023; U.S. edition published by Monthly Review Press 2024.
Keywords: Singh, Bhagat / 1907-1931; Singh, Bhagat / 1907-1931 / Correspondence; India / Politics and government / 1919-1947; India / History / Autonomy and independence movements; Nationalism / India / History; India / History / British occupation, 1765-1947; Inde / Politique et gouvernement / 1919-1947; Inde / Histoire / 1765-1947 (Occupation britannique)